Pricing when customers have limited attention - Tamer Boyacı; Yalçın Akçay (European School of Management and Technology (ESMT), 2017)
We study the optimal pricing problem of a firm facing customers with limited attention and capability to process information about the value (quality) of the offered products. We model customer choice based on the theory of rational inattention in the economics literature, which enables us to capture not only the impact of true qualities and prices, but also the intricate effects of customer's prior beliefs and cost of information acquisition and processing. We formulate the firm's price optimization problem and characterize the pricing and revenue implications of customer's limited attention. We test the robustness of our results under various modelling generalizations such as prices signaling quality and customer heterogeneity, and study extensions such as multiple products, competition, and joint inventory and pricing decisions. We also show that using alternative pricing policies that ignore the limited attention of customers or their ability to allocate this attention judiciously can potentially lead to significant profit losses for the firm. We discuss the managerial implications of our key findings and prescribe insights regarding information provision and product positioning.
Older version: http://hdl.handle.net/10419/129123
Keywords: 650; pricing; choice behavior; rational inattention; information acquisition; signaling game